МОРФОЛОГИЧЕСКИЕ И ГЕНЕТИЧЕСКИЕ ОСОБЕННОСТИ РЯПУШКИ (COREGONIDAE: COREGONUS SP.) ОЗЕРА СОБАЧЬЕ (ПЛАТО ПУТОРАНА) - БОРОВИКОВА ЕЛЕНА АЛЕКСАНДРОВНА; РОМАНОВ ВЛАДИМИР ИВАНОВИЧ; НИКУЛИНА ЮЛИЯ СЕРГЕЕВНА (Общество с ограниченной ответственностью «Эко-Вектор», 2016)
Анализ особенностей морфологии и полиморфизма митохондриальной ДНК (мтДНК) ряпушки (Coregonus sp.) оз. Собачье (плато Путорана) показал значительную близость этой популяции ряпушке европейских водоемов Coregonus albula (Linnaeus). Полученные данные позволяют обсуждать ряд гипотез о происхождении собачинской ряпушки и ее филогенетических взаимоотношениях с ряпушкой Европы и Сибири. Background. Recently was revealed that cisco from Lake Sobachye (Putorana Plateau) is more similar to Coregonus albula Linnaeuas than C. sardinella Valenciennes according to number of vertebrae [13]. The aim of this work was to investigate molecular genetic features of this population. Materials and methods. For morphological analysis were used 60 specimens of cisco from Lake Sobachye. For nine specimens molecular genetic analysis was performed. The sequences of two fragments of the mitochondrial DNA (ND1 and COI) were defined. Results. The cisco of the Lake Sobachye significantly differed from riverine cisco of this region by meristic features (namely from cisco of the River Pyasina). Sequencing results showed the minimal divergence of the ND1 and COI sequences of the cisco from Lake Sobachye and vendace. Conclusion. Morphological analysis and analysis of the mitochondrial DNA polymorphism of cisco from Lake Sobachye revealed close relationship of this population to C. albula.